KEWENANGAN HAKIM MELAKUKAN PENAHANAN TERHADAP TERDAKWA YANG DALAM PERKARA SEBELUMNYA KEBERATAN TERDAKWA/PENASIHAT HUKUM DITERIMA - Susilo, Erwin; Sembiring, Eddy Daulatta (Jurnal Yuridis, 2024)
In cases where the objection raised by the Defendant/Legal Advisor is accepted, the Defendant must be released from detention, allowing the Public Prosecutor to initiate a fresh prosecution with an amended indictment. Challenges arise during re-prosecution concerning the authority of the District Court Judge to order detention. This research adopts a normative legal approach. The findings indicate that, firstly, the District Court Judge lacks the authority to detain the Defendant, as the release from detention resulted solely from an error by the Public Prosecutor in indictment preparation. Re-detention by the District Court Judge is deemed a violation of the presumption of innocence and the principle of equality before the law. Secondly, future reforms to the Criminal Procedure Code should encompass provisions for the release of the Defendant from detention upon acceptance of objection, coupled with a confirmation of the District Court Judge's non-authorization to detain in the subsequent case. This study recommends a reform of the Indonesian Criminal Procedure Code (KUHAP) to enhance legal certainty regarding the detention of the Defendant in subsequent cases. Keywords: Indictment, Objection, Detention, Public Prosecutor, and Defendant.